Physico-Chemical, Microbiological and Sensory Properties of Chicken Meat Balls incorporated with Soy-Protein Concentrate - Bhaskar, K.; Rao, V. Kesava; Kumar, M. Shashi (Journal of Meat Science, 2017)
The physico-chemical, microbiological and sensory parameters of soy protein concentrate (SPC) incorporated (10, 20 and 30%)chicken meat balls were studied at different storage intervals under refrigeration (4±1°C). Cooking yield and gain in weight was highest while shrinkage was less for 30% SPC added chicken meat balls, Proximate composition revealed an increased protein and ash percent and decreased ether extract with significant variation in moisture content with increased incorporation levels of SPC. TBA value decreased significantly while pH showed no significant variation with increasing levels of SPC. However,total viable counts, coliforms, yeast and mould were observed only on 7th day of storage. Moreover, all the three counts increased significantly (p
Keywords: Soy Protein concentrate; Chicken meat balls